Pengaruh Frekuensi Rapat Komite Audit, Ukuran Dewan Komisaris Independen, dan Kompensasi Eksekutif Terhadap Pengungkapan Hal Utama Audit - Birgitta Hilda Wenimeliarita; Nurhafifah Amalina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of Audit Committee Meeting Frequency, the Size of Independent Commissioners, and Company Complexity on the disclosure of Key Audit Matters, with Company Size and Company Complexity as control variables. The sample was selected using purposive sampling based on secondary data, namely financial statements and annual reports of non-cyclical subsector companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The final sample consists of 62 companies, resulting in 186 observations, which were analyzed using EViews 9. The results indicate that executive compensation has a significant effect on the disclosure of Key Audit Matters. This finding suggests that executive compensation provided by the company to key management personnel can offer additional information to external auditors, enabling them to expand audit procedures when considering topics to be disclosed as Key Audit Matters.